Richard von Coudenhove-Kalergi. A re-reading for the future of Europe - Luise, Gianluca (Frontiers in Political Science, 2025)
Although it has not yet found its full recognition and implementation, Kalergi's thought represents a turning point in thinking about the state in the contemporary era. His project of Pan-Europe, described by many as merely utopian, represents a first concrete attempt to redefine statehood in a supranational key. The article investigates the contents of his thought and brings to light the extent to which his legacy continues to influence today's political debate on European integration, offering suggestions on the current challenges related to the relationship between national sovereignty and European institutions.